Perlindungan Hukum Terhadap Penderita Gangguan Jiwa Dalam Pelayanan Kesehatan Sesuai Dengan Peraturan Perundang-Undangan Di Indonesia - Ningsih, Siska Ayu; Shinta, Shinta (Jurnal Ners, 2023)
This study discusses legal protection for people with mental disorders in health services. The purpose of this study is to determine the synchronization of legal protection arrangements for people with mental disorders and their forms of legal protection in health services in the structure of Indonesian laws and regulations. This study used normative juridical research methods The approach method used is the statutory approach (Statue Approach) and analytical approach (Analytical Approach) with the specification of research inventory of laws and regulations, legal synchronization, and legal discovery in concreto. . Based on the results of the research conducted, it was found that the regulation of legal protection for people with mental disorders in health services in the structure of Indonesian laws and regulations has shown a level of synchronization. That is, the lower regulations are in accordance with the higher regulations and the higher regulations are the basis for the formation of lower regulations. Forms of legal protection for people with mental disorders in health services in the structure of Indonesian laws and regulations include: Guarantee of health service arrangements in health care facilities that are easily accessible and in accordance with mental health service standards, achieving the best quality of life and enjoying a healthy mental life, free from fear, freeing ODGJ from shackling, rehabilitation and empowerment of ODGJ, Mental health examination for defendants and victims as well as defendants and plaintiffs with indications of mental disorders for legal purposes, availability of psychopharmaceutical drugs according to their needs, obtaining approval for medical actions, honest and complete information about their mental health data, getting protection from every form of neglect, violence, exploitation,. as well as discrimination, obtaining social needs according to the level of mental illness, managing their own property, obtaining rights as patients in hospitals, equal rights as citizens and equal treatment in every aspect of life.